"List do rodzin" "Gratissimam sane" Jana Pawła II - ciągle aktualne wezwanie = "Gratissimam sane" - John Paul II`s "Letter to Families" - an appeal valid forever - Zydek, Sylwia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
"Letter to Families" was published over 20 years ago, in 1994. It may be read as an attempt to interpret family situation then but also as recipe of a present happy family life. The term letter itself brings to mind words addressed to a friend, a closed person to share joy, important information or exchange thoughts with.
Keywords: Jan Paweł II, papież (1929-2005); John Paul II; etyka chrześcijańska; rodzina; Christian ethics; family